2005
DOI: 10.1007/s10593-005-0192-6
|View full text |Cite
|
Sign up to set email alerts
|

Silyl Modification of Biologically Active Compounds. 10. Lipid Type Organosilicon Derivatives of 8-Hydroxyquinoline and N-(2-Hydroxyethyl)-1,2,3,4-tetrahydro(sila, iso)quinolines

Abstract: As a result of numerous investigations [1][2][3][4][5][6][7][8][9][10] it has been shown that silylation significantly increases the lipophilicity of biologically active compounds and therefore assists their transport within the organism. This is true not only in relation to reversibly silylated (hydrolytically unstable) compounds but also to compounds containing a triorganosilyl(oxy) group stable to hydrolysis under physiological conditions. According to literature data certain tetrahydro(iso)quinoline-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…To overcome the problem of colloid system stability the parent alkanolamine has been modified by introduction of organosilicon substituent and by preparing of salt of silyl modified substance. Introduction of organosilicon substituent into the molecule of alkanolamine is an attractive and original approach to the lipophilicity increase [12][13][14][15] interaction with lipophilic chains of the first coating. The transformation of the compounds into salts in many cases causes activity increase, but also changes (increases) the solubility of the compounds in water, that is very significant for preparing and stabilization of water bilayer colloid systems, used for biological purposes.…”
mentioning
confidence: 99%
“…To overcome the problem of colloid system stability the parent alkanolamine has been modified by introduction of organosilicon substituent and by preparing of salt of silyl modified substance. Introduction of organosilicon substituent into the molecule of alkanolamine is an attractive and original approach to the lipophilicity increase [12][13][14][15] interaction with lipophilic chains of the first coating. The transformation of the compounds into salts in many cases causes activity increase, but also changes (increases) the solubility of the compounds in water, that is very significant for preparing and stabilization of water bilayer colloid systems, used for biological purposes.…”
mentioning
confidence: 99%
“…The separation of the products of the alkylation reaction of N-(2-hydroxyethyl)-1,2,3,4-tetrahydroisoquinoline (1) on silica gel using ethyl acetate gave the N-(2-acetoxyethyl)-1,2,3,4-tetrahydroisoquinoline (3) [3].…”
mentioning
confidence: 99%
“…The N-(2-hydroxyethyl)-1,2,3,4-tetrahydroquinoline (4) [3] is similarly acetylated to give the acetate 5. Unexpectedly, we found that the methyl ether of the N-(2-hydroxyethyl)-1,2,3,4-tetrahydroisoquinoline 2 [4] was also converted to the acetate 3 in 25% yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation